Cost Effectiveness of Latest Recommendations for Group B Streptococci Screening in the United States. Issue 4 (April 2020) - Williams, Marvin; Zantow, Emily; Turrentine, Mark
Abstract : OBJECTIVE: To evaluate whether group B streptococci (GBS) screening using the 2010 guideline (screening at 35 0/7–37 6/7 weeks of gestation) compared with the 2019 guideline (screening at 36 0/7–37 6/7 weeks of gestation with re-screening of women with GBS-negative results 5 weeks later) was more cost effective. METHODS: We constructed a decision-analysis model to compare the outcome of GBS early-onset disease in a hypothetical cohort of 3, 614, 049 women at 35 0/7 weeks of gestation or greater (the number of live births in 2017 excluding births based on population frequency from 23 to 34 weeks of gestation, women with GBS bacteriuria during the current pregnancy, and those with a history of a previous neonate with GBS disease). We took both a health care and societal perspective and all costs were expressed in 2017 U.S. dollars. Effectiveness was based on neonatal quality-adjusted life years (QALYs) gained. An incremental cost-effectiveness ratio was estimated with a willingness to pay threshold set at 100, 000/QALY. All model inputs were derived from the literature. One-way probability and cost sensitivity analysis were performed to investigate model assumptions. RESULTS: Screening at 36 0/7–37 6/7 weeks of gestation with re-screening of women with GBS-negative results if 5 weeks passed from culture to delivery resulted in a 6% increase in neonatal QALYs gained (2, 162 vs 2, 037), 12% fewer cases of neonatal death (30 vs 34), and a 10% estimated reduction in total societal health care expenditures related to GBS early-onset disease (639 million vs 707 million) when compared with the 2010 strategy of only screening at 35 0/7–37 6/7 weeks of gestation. The 2019 approach was cost effective, with an incremental cost-effectiveness ratio of 43, 205 per neonatal QALY gained. CONCLUSION: Screening at 36 0/7–37 6/7 weeks of gestation with a 5-week re-screening for women with GBS-negative results is more cost effective than past strategies used in the United States. Abstract : New recommendations for group B streptococci screening in the United States are estimated to result in fewer cases of neonatal death and lower societal health care expenditures.